Facies Models 9. Eolian Sands - Walker, Roger; Middleton, Gerard (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1977)
Summary Facies models for extensive eolian sand deposits must be based on the characteristics of modern ergs ("sand seas"). Peripheral areas of ergs, where supply of sand is sparse, are characterized by barchansand longitudinal dunes: neither of these seems very likely to be preserved in the geological record. The central parts of ergs, where accumulated sand thickness reaches several hundred metres, are composed of complex pyramidal dunes (draas) with superimposed complex transverse dune types. Almost nothing is known by direct observation of the cross-bedding formed in such dunes, but it is possible that it is not as variable as the complex external morphology might suggest. Identification of ancient sandstone formations as eolian is based mainly upon one major criterion: the very large scale and relatively high angle of the cross-bedding. In many cases minor indicators, such as eolian ripples (orientated at large angles to the trend of the major foresets), avalanch scours, animal tracks, soft-sand faults, raindrop impressions, etc., are also present. Negative evidence is equally important: the only known alternative model, that of a submarine tidal sand-wave field, is not known to produce large scale, high angle cross-bedding: it probably produces medium-scale cross-bedding resulting mainly from migration of megaripples or sand waves of relatively small scale, superimposed on the large scale features. The cross-bedding probably shows at least some bipolar orientation of cross-bed directions, a feature absent from all classic ancient eolian sandstones. Furthermore, in the tidal sand wave model, sand deposits are associated with muddy sediments bearing a marine fauna, and this is not the case in the classic ancient eolian sandstones of the western U.S.A. and elsewhere.